A HANK2 model of monetary unions - Christian Bayer; Alexander Kriwoluzky; Gernot J. Müller; Fabian Seyrich (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
How does a monetary union alter the impact of business cycle shocks at the household level? We develop a Heterogeneous Agent New Keynesian model of two countries (HANK2) and show in closed form that a monetary union shifts the adjustment to a shock horizontally - across countries - within the brackets of the union-wide wealth distribution rather than vertically - that is, across the brackets of the union-wide wealth distribution. Calibrating the model to the euro area reveals that a monetary union alters the impact of shocks most strongly in the tails of the wealth distribution but leaves the middle class almost unaffected.
Keywords: F45; E52; D31; 330; HANK2; OCA theory; Two-country model; monetary union; spillovers; monetary policy; heterogeneity; inequality; households